Clinical Considerations for the Management of Advanced PD-L1 ≥50% Non-small Cell Lung Cancer In 2025: Should All Patients Be Treated the Same? (Canadian Oncology Today, 2025)
Despite advances in the treatment of non‑small cell lung cancer (NSCLC) due to the advent of immunotherapy in the form of immune checkpoint inhibitors (ICI), NSCLC remains the leading cause of cancer-related death in Canada. In addition, multiple first‑line options exist for patients with NSCLC without a sensitizing mutation in epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK), but no head‑to‑head comparisons of first-line treatment regimens have been made in randomized controlled trials. The programmed cell death ligand 1 (PD-L1) tumour proportion score (TPS)—which is derived from immunohistochemistry analysis—emerged as an important biomarker early in the advent of ICI in NSCLC. Approximately 30% of patients with NSCLC have PD-L1 expression in at least 50% of the tumour. This ≥50% threshold was established through retrospective biomarker analyses in pivotal trials, such as the KEYNOTE-001 and KEYNOTE-024 trials, in which patients with higher PD-L1 expression demonstrated superior response rates and overall survival (OS) benefits with immunotherapy compared to chemotherapy. The KEYNOTE-001 trial first identified ≥50% PD-L1 expression as an optimal cut-off for predicting response to pembrolizumab (anti-programmed cell death protein 1 [PD-1] antibody), showing an objective response rate (ORR) of ~45% in this group. Subsequently, the KEYNOTE-024 trial confirmed that patients with PD-L1 ≥50% had significantly improved progression-free survival (PFS) and OS with pembrolizumab than those treated with chemotherapy (hazard ratio [HR] for PFS: 0.50, 95% confidence interval [CI]: 0.37–0.68). Similar findings from the IMpower110 (atezolizumab) and EMPOWER-Lung 1 trials (cemiplimab) reinforced ≥50% PD-L1 TPS as a clinically meaningful biomarker. As a result, ≥50% PD-L1 TPS became an actionable biomarker in regulatory approvals and treatment guidelines, guiding immunotherapy decisions in advanced NSCLC.